Application of Information Processing System Based on DSP in Electronic Information Engineering. Issue 1 (1st February 2022) - Huang, Jingbo
Abstract: On the one hand, target tracking technology is widely used in navigation, guidance, alarm and monitoring and other military fields, on the other hand, it is also widely used in civil fields such as traffic information monitoring and security. This paper mainly studies the application of information processing system based on DSP in electronic information engineering. This paper introduces DSP information processing system in detail. Aiming at the comprehensive requirements of real-time and tracking performance of the target tracking system, multi-feature fusion optimization method is adopted to improve the particle filter tracking algorithm to improve the accuracy of the tracking algorithm. In this paper, the simulation results show that the improved algorithm has a certain scale and occlusion robustness, and can adapt to long-term stable real-time tracking.